DFB diode seeded low repetition rate fiber laser system operating in burst mode. (February 2017) - Šajn, M.; Petelin, J.; Agrež, V.; Vidmar, M.; Petkovšek, R.
Abstract: A distributed feedback (DFB) diode, gain switched to produce pulses from 60 ps at high peak power of over 0.5 W, is used in burst mode to seed a fiber amplifier chain. High seed power, spectral filtering between amplifier stages and pulsed pumping are used to mitigate amplified spontaneous emission (ASE). The effect of pulse pumping synchronized with the seed on the ASE is explored for the power amplifier at low repetition. Different input and output energies at different burst repetition rates are examined and up to 85% reduction in ASE is achieved compared to continuous pumping. Finally, a numerical model is used to predict further reduction of ASE. Highlights: A DFB diode driven to produce pulses in 10 s of ps with peak powers over 0.5 W. Preshaped bursts amplification at low repetition rate. A theoretical and experimental study of the effect of pulsed pumping on the ASE. ASE reduction using synchronous pulsed pumping up to 85%.